2024
DOI: 10.24084/repqj12.460
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Emission of Large PV Installations Case Study of a 1 MW Solar Campus

Abstract: Abstract. Extensive measurements were carried out at a 1 MW photovoltaic (PV) installation with focus on the analysis of harmonic emission both for classical harmonics below 2.5 kHz and higher frequency emission in the range of 2-150 kHz. The installation consists of multiple inverters with different rated power. Beside the measurement of total emission of all inverters, in one part of the measurement the inverters were switched off and on stepwise following a predefined schedule. This provides a comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 3 publications
2
13
0
Order By: Relevance
“…In order to validate the proposed model and simulation results, we shall relate our findings to those of existing models. In [27], [28], and [29], both simulations and field tests results showed that the harmonic currents generation associated with grid connected PV systems are strongly correlated with the grid voltage harmonics present. In [27], SPICE simulator was used for simulations and experiments were also conducted to verify the results.…”
Section: Proposed Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to validate the proposed model and simulation results, we shall relate our findings to those of existing models. In [27], [28], and [29], both simulations and field tests results showed that the harmonic currents generation associated with grid connected PV systems are strongly correlated with the grid voltage harmonics present. In [27], SPICE simulator was used for simulations and experiments were also conducted to verify the results.…”
Section: Proposed Model Validationmentioning
confidence: 99%
“…Authors concluded that the nature of harmonic currents from grid integrated PV systems were dependent on the grid voltage condition. Similarly, [28], and [29] performed measurements and thereafter deployed some modelling and simulations (using the phasor domain approach) to verify their results. The notion of 'phase angle diversities and summation exponent' were also suggested by [29] in order to assess the harmonic interactions between the grid and the PV system in their model.…”
Section: Proposed Model Validationmentioning
confidence: 99%
“…Most of the continuous control methods use powerelectronic converters that introduce harmonics into the grid. Especially an increase in the emission of supraharmonics is expected [29].…”
Section: ) Harmonic Distortionmentioning
confidence: 99%
“…With increasing proliferation of VSCbased converters, particularly in distributed generation, their harmonic impact on the grid needs to be more closely scrutinized. In particular, it has been frequently observed that current harmonics injected by power converters largely depend on the background voltage harmonics [5], [6], even in the absence of significant grid impedances. In the presence of grid impedances, harmonic currents injections from converters can alter voltage harmonics at the connection point, due to the voltage drop imposed by the grid impedances.…”
Section: Introductionmentioning
confidence: 99%